Challenges and Solutions of Cyber Crime in Indian Jurisprudence: Bridging the Gap: Strengthening India's Legal Response to Cyber Crime (Journal of Advances and Scholarly Researches in Allied Education, 2023)
There is a balance of good and evil in life. The web is, too. Cyberspace has many positiveuses, but it also has some negative ones. However, since there are no police officers monitoring theInternet as there are in traditional neighborhoods, anything from Trojan horses and viruses to cyberstalking, trademark counterfeiting, and cyber terrorism may flourish online. If we want to avoid becomingvictims of online crime, now is the moment to educate ourselves on the dangers posed by bothdeliberate and careless actions. Cybercrime is a product of technology, and without it, its investigationand regulation would be impossible. Although India's legal system is inadequate at the present, it mayserve as a powerful deterrence against such acts..